Coat color and morphological hair traits influence on the mechanisms related to the heat tolerance in hair sheep - Leite, Jacinara Hody Gurgel Morais; Da Silva, Roberto Gomes [UNESP]; Asensio, Luis Alberto Bermejo; de Sousa, José Ernandes Rufino; da Silva, Wallace Sostene Tavares; da Silva, Wilma Emanuela; Façanha, Débora Andrea Evangelista (Springer Nature, 2020)
The principal focus of this study was to describe how the coat characteristics could affect the heat exchanges in animals managed in a hot environment. The Morada Nova ewes were monitored once a month, during 10 consecutive months, in three commercial flocks. Initially, an analysis was performed to measure the differences regarding the coat color in the thermoregulation mechanisms. The animals were grouped into 4 different groups according to coat tonality, as follows: dark red animals (group 1, N = 23), intermediate red color (group 2, N = 27), light red animals (group 3, N = 30), and white-coated animals (group 4, N = 30). The data were collected from 1100 to 1400 h, after the animals were exposed to 30 min of direct sunlight. The cluster analysis was performed considering the hair structural characteristics such as coat thickness (CT, cm), hair length (HL, mm), hair diameter (HD, m), and number of hairs (NH, hairs per unit area), after that these clusters were compared in relation to thermoregulatory mechanisms that include rectal temperature (RT, °C), respiratory rate (RR, breaths min−1), cutaneous evaporation (CE, °C), and respiratory evaporation (RE, W m−2). The groups were characterized and compared using mean and standard deviation, and the differences between the clusters were compared using the Tukey test with a 5% probability of error. In relation to coat color, no differences were found in groups 1, 2, and 3 regarding the activation of the thermoregulation mechanisms. The most different was observed in the totally white coat that presented different thermoregulatory responses as the highest sweating rate. White-coated animals showed a non-pigmented epidermis, and the hair structure is responsible to promote skin protection as necessary, such as a dense coat (1242.7 hair cm−2), long hair (14.2 mm), and thicker coat (7.38 mm). In red-coated animals, the hair structure favored heat loss to the environment, such as short hairs, less thick coat, and less hairs per square centimeter. All evaluated animals showed the rectal temperature within the reference limits for the ovine species, regardless of the coat color. In the analysis of clusters related to the physical structure of hair, it was possible to observe that the animals with thick hair, short hair, and less dense coat tended to have a higher capacity to eliminate heat through their respiratory rate and showed less intense heat loss by cutaneous evaporation. We verified that coat color presents a direct influence on the hair structure and the activation of mechanisms related to thermoregulation.
Keywords: Cutaneous evaporation; Homeothermy; Locally adapted breed; Thermoregulatory mechanisms